Has Covid-19 really moved education to 4IR where learning will be digital, with a few occasions of face-to-face engagements? - Motau, Vincent (Journal of Sustainable Development Law and Policy, 2025)
The outbreak of the Covid-19 pandemic had an impact on institutions of higher learning in Africa. As a result, the government introduced a new system of learning that led the institutions of higher learning to shift away from physical or face-to-face teaching and learning to online. This made some of the universities comprehend that online learning is doable in Africa. The aim of this study is to examine whether Covid-19 really moved education to 4IR where learning will be digital, with a few occasions of face-to-face engagements? This paper followed a qualitative methodology and was guided by an exploratory research design. The data was collected from 25 participants who were selected purposively. The collected data was transcribed using Microsoft Word and analyzed using thematic content analysis. A key finding of this paper is that the lectures and students were inconvenienced by the introduction of online learning and teaching. Most of the academic institutions still prefer physical learning because it is effective and affordable. This paper recommends that a hybrid approach of teaching and learning be adopted as the digital system should also not be abandoned post-COVID-19 because it makes it easier to conduct teaching and learning in institutions of higher learning.